Communicating uncertainties in climate findings – Exploring the case of sea level rise adaptation in Sweden - Al-Lazkani,Ahmad (2025)
Climate change poses significant challenges, demonstrated by climate threats that are becoming increasingly severe and frequent. This creates a higher need for uncertainty communication that considers risk-based decision-making. Global climate research, synthesised by the Intergovernmental Panel on Climate Change (IPCC), is a starting point for regional climate assessments, for which the Swedish Meteorological and Hydrological Institute (SMHI) is a main producer. These assessments, in turn, provide climate information to various users in Sweden. Uncertainty signifies this entire process and can be conveyed through the IPCC’s probability estimates, which have been identified to have strengths and limitations. In order for climate information to be useful for the user, uncertainties must be characterised and presented in ways that support decision-making. This thesis focuses on sea-level adaptation due to identified uncertainties in relation to various climate projections. The purpose of the thesis is to explore how the communication of climate uncertainties from IPCC research can inform decision-making, the way Swedish authorities quantify and manage uncertainties related to sea-level rise, and how climate information can be adapted to users' needs in climate adaptation.
Keywords: Uncertainty; IPCC; climate scenarios; climate adaptation; robust decision-making; sea-level rise.